A Soft Total Artificial Heart—First Concept Evaluation on a Hybrid Mock Circulation. Issue 10 (10th July 2017) - Cohrs, Nicholas H.; Petrou, Anastasios; Loepfe, Michael; Yliruka, Maria; Schumacher, Christoph M.; Kohll, A. Xavier; Starck, Christoph T.; Schmid Daners, Marianne; Meboldt, Mirko; Falk, Volkmar; Stark, Wendelin J.
Abstract: The technology of 3D‐printing has allowed the production of entirely soft pumps with complex chamber geometries. We used this technique to develop a completely soft pneumatically driven total artificial heart from silicone elastomers and evaluated its performance on a hybrid mock circulation. The goal of this study is to present an innovative concept of a soft total artificial heart (sTAH). Using the form of a human heart, we designed a sTAH, which consists of only two ventricles and produced it using a 3D‐printing, lost‐wax casting technique. The diastolic properties of the sTAH were defined and the performance of the sTAH was evaluated on a hybrid mock circulation under various physiological conditions. The sTAH achieved a blood flow of 2.2 L/min against a systemic vascular resistance of 1.11 mm Hg s/mL (afterload), when operated at 80 bpm. At the same time, the mean pulmonary venous pressure (preload) was fixed at 10 mm Hg. Furthermore, an aortic pulse pressure of 35 mm Hg was measured, with a mean aortic pressure of 48 mm Hg. The sTAH generated physiologically shaped signals of blood flow and pressures by mimicking the movement of a real heart. The preliminary results of this study show a promising potential of the soft pumps in heart replacements. Further work, focused on increasing blood flow and in turn aortic pressure is required.